USEFUL PROPERTIES OF THE TROPHY PLANT - Abdug'aniyeva Feruza Zayirkulovna (Лучшие интеллектуальные исследования, 2023)
Abstract: This scientific article provides information on the beneficial properties of Jerusalem artichoke, that is, earth pear.